VARIASI RASIO BAHAN PENSTABIL CMC (Carboxy Methyl Cellulose) DAN GUM ARAB TERHADAP MUTU VELVA ALPUKAT (Parsea americana Mill.) - tantono, Erwin; Effendi, Raswen; Hamzah, Farida Hanum (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research to obtain the best concentration ratio of stabilizer CMC and gum arabic in making of avocado velva. This research used Completely Randomized Design (CRD) with five treatments and three replications followed by DNMRT test at 5% level. The treatments in this research was CG1(stabilizer CMC:arabic gum=0:1), CG2 (stabilizer CMC:arabic gum= 1:2), CG3 (stabilizer CMC:arabic gum= 1:1), CG4 (stabilizer CMC:arabic gum= 2:1) dan CG5 (stabilizer CMC:arabic gum=1:0). The result of analyis of variance showed that variations combination of stabilizer CMC and gum arabic has significantly affected the overrun, melting rate, total dissolved solid and sensory value on descriptive and hedonic attribute texture. Variations ratio of stabilizer CMC and gum arabic on descriptive and hedonic did not significantly affected attribute colour, flavour and taste of avocado velva. The best treatment in this research was CG4 (stabilizer CMC:arabic gum= 2:1) with overrun 20.30%, melting rate 24.19 minutes, total dissolved solid 32.12 °brix, yellow colour, avocado flavour, avocado taste and soft texture. Keywords: velva, CMC, gum arabic